(untitled) (International journal of artificial intelligence, 2025)
In this article, the level of salinity of irrigated areas of Bukhara region and the melioration of irrigated lands in Kogon district, as well as the Korak collector-zovur network, which serves inter-households in the district, are studied and analyzed. Also, the authors commented on the positive and negative aspects of this collector.